Media effects : advances in theory and research - Bryant, Jennings, 1944-; Oliver, Mary Beth, ....- (New York : Routledge, 2009)
With contributions from some of the finest scholars in the discipline, Media Effects serves not only as a comprehensive reference volume for media effects study but also as an exceptional textbook for advanced courses in media effects. Covering the breadth of the media effects arena, this third edition provides updated material as well as new chapters focusing on effects of mobile media and other technologies. As this area of study continues to evolve, Media Effects will serve as a benchmark of theory and research for current and future generations of scholars.
Includes bibliographical references and indexes.
Keywords: Communicatie : mass media; Mass media -- Political aspects -- United States; Mass media -- Social aspects -- United States; Mass media -- Influence -- United States; Mass media -- Psychological aspects -- United States